In female rat heart mitochondria, oophorectomy results in loss of oxidative phosphorylation. Issue 2 (February 2017) - Pavón, Natalia; Cabrera-Orefice, Alfredo; Gallardo-Pérez, Juan Carlos; Uribe-Alvarez, Cristina; Rivero-Segura, Nadia A; Vazquez-Martínez, Edgar Ricardo; Cerbón, Marco; Martínez-Abundis, Eduardo; Torres-Narvaez, Juan Carlos; Martínez-Memije, Raúl; Roldán-Gómez, Francisco-Javier; Uribe-Carvajal, Salvador
Abstract : Oophorectomy in adult rats affected cardiac mitochondrial function. Progression of mitochondrial alterations was assessed at one, two and three months after surgery: at one month, very slight changes were observed, which increased at two and three months. Gradual effects included decrease in the rates of oxygen consumption and in respiratory uncoupling in the presence of complex I substrates, as well as compromised Ca 2+ buffering ability. Malondialdehyde concentration increased, whereas the ROS-detoxifying enzyme Mn 2+ superoxide dismutase (MnSOD) and aconitase lost activity. In the mitochondrial respiratory chain, the concentration and activity of complex I and complex IV decreased. Among other mitochondrial enzymes and transporters, adenine nucleotide carrier and glutaminase decreased. 2-Oxoglutarate dehydrogenase and pyruvate dehydrogenase also decreased. Data strongly suggest that in the female rat heart, estrogen depletion leads to progressive, severe mitochondrial dysfunction.